2013
DOI: 10.1007/s12264-013-1392-1
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cell microchimerism in the maternal mouse spinal cord

Abstract: Fetal cell microchimerism refers to the persistence of fetal cells in the maternal tissues following pregnancy. It has been detected in peripheral organs and the brain, but its existence in the spinal cord has not been reported. Our aim was to detect fetal cell microchimerism in the spinal cord of maternal mice. C57BL/6 female mice were crossed with GFP transgenic male mice and sacrificed after their first or third delivery. GFP-positive cells, which were presumably from fetuses whose fathers were GFP transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Fetal cells cross the placental barrier and enter the maternal circulation, where they can survive, migrate, and integrate into different maternal tissues ( Zeng et al., 2010 ). In animal models, FMc has been detected in various organs such as the bone marrow ( Fujiki et al., 2008 , 2009 ; Khosrotehrani et al., 2008 ; Pritchard et al., 2012 ), pituitary gland ( Jimenez et al., 2005 ), skin ( Jimenez et al., 2005 ; Aractingi et al., 2002 ), appendix ( Santos et al., 2008 ), liver ( Beksac et al., 2020 ; Fujiki et al., 2008 , 2009 ; Jimenez et al., 2005 ; Khosrotehrani et al., 2008 ; Wang et al., 2004 ), brain ( Dawe et al., 2007 ; Zeng et al., 2010 ; Tan et al., 2005 ), lung ( Fujiki et al., 2008 , 2009 ; Pritchard et al., 2012 ), heart ( Fujiki et al., 2008 , 2009 ; Jimenez et al., 2005 ; Kara et al., 2012 ), spinal cord ( Zhang et al., 2014 ), suprarenal gland ( Jimenez et al., 2005 ), kidney ( Fujiki et al., 2008 , 2009 ; Wang et al., 2004 ), spleen ( Fujiki et al., 2008 , 2009 ; Jimenez et al., 2005 ; Khosrotehrani et al., 2008 ), thyroid ( Imaizumi et al., 2002 ; Jimenez et al., 2005 ), lymph nodes ( Jimenez et al., 2005 ; Nguyen Huu et al., 2006 ), thymus ( Fujiki et al., 2008 , 2009 ; Khosrotehrani et al., 2008 ) and pancreas ( Vojdani et al., 2018 ) ( Figure 4 ).
Figure 4 Fetal microchimerism (FMc) presence in rodent organs and associated diseases Representation of the different rodent organs where FMc have been identified and the associated diseases where FMc have been localized.
…”
Section: Detection and Characterization Of Fmc In Animal And Human Maternal Tissuesmentioning
confidence: 99%
“…Fetal cells cross the placental barrier and enter the maternal circulation, where they can survive, migrate, and integrate into different maternal tissues ( Zeng et al., 2010 ). In animal models, FMc has been detected in various organs such as the bone marrow ( Fujiki et al., 2008 , 2009 ; Khosrotehrani et al., 2008 ; Pritchard et al., 2012 ), pituitary gland ( Jimenez et al., 2005 ), skin ( Jimenez et al., 2005 ; Aractingi et al., 2002 ), appendix ( Santos et al., 2008 ), liver ( Beksac et al., 2020 ; Fujiki et al., 2008 , 2009 ; Jimenez et al., 2005 ; Khosrotehrani et al., 2008 ; Wang et al., 2004 ), brain ( Dawe et al., 2007 ; Zeng et al., 2010 ; Tan et al., 2005 ), lung ( Fujiki et al., 2008 , 2009 ; Pritchard et al., 2012 ), heart ( Fujiki et al., 2008 , 2009 ; Jimenez et al., 2005 ; Kara et al., 2012 ), spinal cord ( Zhang et al., 2014 ), suprarenal gland ( Jimenez et al., 2005 ), kidney ( Fujiki et al., 2008 , 2009 ; Wang et al., 2004 ), spleen ( Fujiki et al., 2008 , 2009 ; Jimenez et al., 2005 ; Khosrotehrani et al., 2008 ), thyroid ( Imaizumi et al., 2002 ; Jimenez et al., 2005 ), lymph nodes ( Jimenez et al., 2005 ; Nguyen Huu et al., 2006 ), thymus ( Fujiki et al., 2008 , 2009 ; Khosrotehrani et al., 2008 ) and pancreas ( Vojdani et al., 2018 ) ( Figure 4 ).
Figure 4 Fetal microchimerism (FMc) presence in rodent organs and associated diseases Representation of the different rodent organs where FMc have been identified and the associated diseases where FMc have been localized.
…”
Section: Detection and Characterization Of Fmc In Animal And Human Maternal Tissuesmentioning
confidence: 99%
“…In one study, it has been de-monstrated that although the frequency of FSCs was higher in murine lungs during pregnancy, the number of fetal cells decreased significantly 21 days after delivery ( 18 ). In a recent study, GFP-positive cells were detected in 20% of the maternal spinal cord in first pregnancy; while it reached to 80% after the third pregnancy percent ( 19 ). Pregnancy-associated progenitor cells which have properties similar to stem cells and are found in injured and/or diseased tissues, persist in maternal blood and organs for decades after delivery ( 3 ).…”
Section: Discussionmentioning
confidence: 91%
“…(B) Murine models have demonstrated fetal placental cells traffic to injured maternal hearts and then give rise to cardiomyocytes, endothelial cells, and smooth muscle cells 56 . In addition, fetal chimeric cells have been reported to adopt diverse cell fates, including lymphocyte, 47 hepatocyte, 48 and neuron 45,46 …”
Section: Consequences and Functional Implicationsmentioning
confidence: 99%
“…The study demonstrated a potential for tissue repair and the possibility of identifying distinct subtypes within fetal microchimeric cells. Additionally, murine fetal microchimeric cells were detected in maternal spinal cord and brain tissue where they adopted neuronal phenotypes, 45,46 indicating that the cells can cross the blood–brain barrier. In murine brains with lesions or injury, fetal cells positioned themselves near blood vessels (but did not adopt an endothelial phenotype) and were found to express neuronal markers, suggesting tissue‐specific differentiation potential.…”
Section: Progress and Benefit Of Fetal Placental Progenitor Cells In mentioning
confidence: 99%